The cultural revolution at the margins : Chinese socialism in crisis - Wu, Yiching (Harvard University Press, 2014)
"The Cultural Revolution began as a "revolution from above," and Mao had only a tenuous relationship with the Red Guard students and workers who responded to his call. Yet it was these young rebels at the grassroots who advanced the Cultural Revolution's more radical possibilities, Yiching Wu argues, and who not only acted for themselves but also transgressed Maoism by critically reflecting on broader issues concerning Chinese socialism. As China's state machinery broke down and the institutional foundations of the PRC were threatened, Mao resolved to suppress the crisis. Leaving out in the cold the very activists who had taken its transformative promise seriously, the Cultural Revolution devoured its children and exhausted its political energy. The mass demobilizations of 1968-69, Wu shows, were the starting point of a series of crisis-coping maneuvers to contain and neutralize dissent, producing immense changes in Chinese society a decade later."--Publisher's description